The Triangle Defense for Financial Reporting Quality: The Interplay between Internal Auditing, the Audit Committee, and the External Auditor - Djoko Susanto (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2020)
The internal audit function, audit committee, and external auditor are three crucial stakeholders of corporate governance that safeguard the quality of financial reporting. In this article, I discuss the interrelationships between these monitoring mechanisms. I also provide insights about what we have learned from academic research about the working relationships between these three governance entities. This article should be of interest to academic researchers as well as to corporate stakeholders, which include management, investors, regulators, and Dewan Komisaris members. Future researchers can make use of this article as they contribute more work in areas related to auditing, monitoring and corporate governance, and financial reporting quality. Insights from this article can also guide corporate stakeholders to assess the effectiveness of the internal audit, audit committee, and external auditors in their organizations.